Apoyo en la supervisión del proyecto Caminos de Esperanza en la empresa ingeniería, arquitectura y proyectos INARPROYECT en Samacá-Boyacá (2022)
The engineering and architecture Enterprise and projects INARPTOYECT S.A.S founded in 2008 provides consultan cies and constructions in the city of Tunja and its surroundings. INARPROYECT S.A.S conducts social interest housing projects, generating both a social and economic impact in the community of the department of Boyacá. Currently, the project Caminos de E speranza is being under execution in Samacá town which consist of building 100 apartments of 60.8 m2 each. Boyacá This document reports the activities in which the practitioner supported the enterprise during the internship executing activities such as supporting, verifying, controlling and tracing Caminos de Esperanza building lot in Samacá.